Potential Blending of Short Residues, Automotive Diesel Oil (ADO) and Kerosene for Marine Fuel Oil (MFO) Low Sulphur 180 Export Quality at PT. XYZ Using H-CAMS Simulation - Saputra, Agung Aldi; Samhani Mahendra Wijaya; Astuti, Erna; Aster Rahayu (Universitas Nusa Bangsa, 2024)
Marine Fuel Oil (MFO) Low Sulfur is a ship fuel for engines that have an rpm <300, which has a maximum sulfur content of 0.5% wt and a Kinematic Viscosity limit at a temperature of 50 ℃ with a maximum of 180 CSt. Blending MFO products has the potential to meet international market demand and optimize sales of MFO products in domestic and international markets. The change in specifications requested by PIMD (P International Marketing & Distribution) refers to the Decree of the Director General of Oil and Gas No. 0179.K/10/DJM.S/2019. This research aims to meet international market demand so that MFO (Marine Fuel Oil) products with new specifications are needed. This research uses a blending optimization method using Short Residue (SR), Automotive Diesel Oil (ADO), and Kerosene (KR) using simulation using H-CAMS software. This research focuses more on the critical values of MFO products, namely Density, Kinematic Viscosity, Flash Point, and Pour Point analysis. The blending simulation process has 12 variations between SR: ADO: KR. As the composition of ADO and Kerosene increases in the blending ratio, it causes a decrease in the Density, Flash Point, Kinematic Viscosity, and Pour Point values. In this research, the most optimum blending formula was found, namely formulas 4, 5, 10, and 11, all critical specifications in the manufacture of the MFO 180 LS product were met except for the Pour Point parameter, so this research needs to be continued by reducing the pour point value.